Spectrophotometric and Spectrofluorimetric Methods for the Determination of Gemifloxacin Mesylate in its Pure and Dosage Forms using Eosin - Ali Al-Tamimi, Salma (Asian Journal of Chemistry, 2013)
Spectrophotometric and spectrofluorimetric methods were developed for the determination of gemifloxacin mesylate (GFX) in dosage forms. The spectrophotometric method (method I) is based on formation of ternary complex with eosin at 543 nm in acetate buffer of pH 4. The absorbance-concentration plot is rectilinear over the range 1-10 μg/mL with LOD of 0.157 μg/mL and LOQ of 0.476 μg/mL. The spectrofluorimetric method (method II) is based on the quantitative quenching effect of gemifloxacin mesylate on the native fluorescence of eosin at the same pH. The quenching of the fluorescence of eosin was measured at 544 nm after excitation at 337 nm. The fluorescence-concentration plot is rectilinear over the range 0.6-4 μg/mL with LOD of 0.108 μg/mL and LOQ of 0.328 μg/mL. The proposed methods were successfully applied to the analysis of tablets of the drug. Statistical comparison of the results with those of the reference method revealed good agreement and proved that there were no significant differences in the accuracy and precision between the two methods respectively.